Towards sustainable mobility – Transformative scenarios for 2034. (December 2022) - Kiviluoto, Katariina; Tapio, Petri; Tuominen, Anu; Lyytimäki, Jari; Ahokas, Ira; Silonsaari, Jonne; Schwanen, Tim
Highlights: Increasing the share of walking and cycling is one of the building blocks of sustainable mobility transformation. We organised an online Delphi survey for 30 walking and cycling experts during the first wave of COVID-19 pandemic. Disaggregative Delphi analysis is elaborated based on the systemic restructuring of qualitative data. Transport experts' views of the future are described in the form of five walking and cycling scenarios up to 2034. The results can be used for strategic transport planning and policy, and for identifying instruments for walking and cycling promotion in urban areas. Abstract: Increasing the share of walking and cycling is one of the building blocks of sustainable mobility transformation. Fundamental changes are needed in society and urban structure to support the integration of walking and cycling into everyday routines. We conducted an online Delphi study with 30 walking and cycling experts during the first wave of the COVID-19 pandemic in Finland in the spring of 2020. The aim was to explore transport experts' views on the future and derive scenarios of walking and cycling with the broader context of the urban mobility system. The scenarios were created using a combination of cluster analysis and qualitative content analysis. In addition, a methodological elaboration of the Disaggregative Delphi analysis was introduced, systematising the analysis of qualitative data. The analysis resulted in five scenarios depicting walking and cycling in 2034: 1. Business as Usual Plus, 2. The Demise of Bus-Transport, 3. The Era of Soft Modes, 4. Public Transport Serving All, and 5. Car-dependent Lifestyles Persist. The scenario set can be used as a basis for strategic transport planning and policy as well as a more practical tool for identifying measures for walking and cycling promotion in urban areas.